2005
DOI: 10.1016/s1015-9584(09)60268-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Electrothermal Vessel Sealing System Versus Standard Vessel Ligation in Thyroidectomy

Abstract: We found that the LigaSure was as safe as standard vessel ligation for thyroidectomy, with the benefit of reduced operating time. A future prospective study has been designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 8 publications
3
34
1
2
Order By: Relevance
“…Several authors reported a reduction in complications such as transient recurrent palsy and transient hypoparathyroidism and shorter operating times, 12 whereas others reported a shorter operating time but no change in the incidence of complications. [13][14][15] Some authors even reported no difference in operating times or the incidence of complications between LigaSure and traditional hemostatic methods. We began using LigaSure in thyroidectomy in 2002.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported a reduction in complications such as transient recurrent palsy and transient hypoparathyroidism and shorter operating times, 12 whereas others reported a shorter operating time but no change in the incidence of complications. [13][14][15] Some authors even reported no difference in operating times or the incidence of complications between LigaSure and traditional hemostatic methods. We began using LigaSure in thyroidectomy in 2002.…”
mentioning
confidence: 99%
“…Several authors 14,15 maintain that LigaSure is suitable for use in hemithyroidectomy, since it makes separating the thyroid gland tissue easier than traditional methods of ligation, thereby reducing the operating time to about 20 min. We do agree that the device may be faster and more effi cient in the early phases of the operation: for coagulating the external jugular veins, for preparing fl aps by separating the platysma, and for separating the strap muscles along the linea alba.…”
mentioning
confidence: 99%
“…De esta forma, si se consideran las cirugías realizadas por los cirujanos del equipo existe una leve disminución en el tiempo operatorio de los pacientes operados con Ligasure, similar a otros reportes internacionales 9 . El hematoma que se presentó en el grupo de Ligasure correspondió a un paciente añoso con arteriosclerosis de Monckeberg confirmada histológicamente.…”
Section: Resultsunclassified
“…Esto, en contraste con el alto costo inicial de la máquina y el costo por cada paciente en el uso de Ligasure, por lo que sólo sería beneficioso en centros que operan un alto número de tiroidectomías al año (> 100) 8,9 . Basados en los resultados expuestos creemos que la tiroidectomía con técnica de sellado de vasos con Ligasure Precise es un método posible de realizar en nuestro medio, siendo tan seguro como la tiroidectomía con ligaduras.…”
Section: Resultsunclassified
“…This is mostly due to imperfect haemostasis as well as the damage to adjacent organs, firstly the nerves. Wide application of the latest techniques provided notable decrease of both intra-and postoperative complication rate (Vassilios et al 2005, Shen et al 2005, Rosato et al 2004). Today, surgical dissection and tissue coagulation with monopolar and bipolar coagulation as well as LigaSure high frequency current generator (HFCG) are the surgical modalities of choice (Andreas 2004, Foster 1978, Dionigi et al 2006).…”
Section: Introductionmentioning
confidence: 99%